Hubungan Keharmonisan Keluarga Dengan Motivasi Belajar Peserta Didik DI SMA Negeri 1 Luwuk - salma, Wiesmayani; lambause, awaldin; Firliani Putri, Dyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2025)
This research aims to determine the relationship between family harmony and students' learning motivation at SMA Negeri 1 Luwuk for the 2024/2025 academic year. This research uses quantitative methods. The sample in this research was class XI students at SMA Negeri 1 Luwuk. Sampling was carried out using a simple random sampling technique. The data collection method is by distributing questionnaires to students as research samples. The analysis used is product moment correlation. The research results show that the correlation coefficient (r) = 0.39242 is a positive number. This shows that the influence of family harmony on learning motivation at SMA Negeri 1 Luwuk is positive. The KD value = 15.4% shows the great influence of family harmony on learning motivation at SMA Negeri 1 Luwuk, which is 15.4%. Meanwhile, the value of Tcount = 2.45, with degrees of freedom (db) = 35 – 2 = 33 and a significance level of 0.05 = 1.69 so, Tcount is greater than Ttable or 2.45 > 1.69, so the correlation is What happens is that there is a relationship between family harmony and motivation to study at SMA Negeri 1 Luwuk. Thus, the hypothesis is accepted. Keywords: Harmony, Family, Learning Motivation